THE EXPERIENCE OF QUALIFICATIONS FRAMEWORK ELABORATION IN THE RUSSIAN FORESTRY SECTOR AS A PART OF THE TEMPUS SUFAREL PROJECT - Eldar A. Kurbanov; Oleg N Vorobiev (Russian State Vocational Pedagogical University, 2015)
The paper deals with qualifications framework development for the Russian forestry sector, carried out in accordance with the Tempus SUFAREL project of the consortium of Russian and EU universities and organizations. The authors emphasize the need for effective estimation and regulation methods based on the competence-oriented qualifications descriptors reflecting the employers' demands. The publication analyzes professional competences formation in European universities, descriptor contents of national qualifications frameworks, education specificity and requirements for the forestry sector in different countries. The research outcomes provide a basis for qualifications framework development in the Russian forestry sector including the main descriptors of responsibility and authority, skills and competences.The authors believe that the above qualifications framework can reinforce qualifications system developments and advanced vocational training, as well as the labor market strategy elaborations.